Teaching Paragraph Writing Through Interactive and Process Approaches - Ajeng Setyorini; Entika Fani Prastikawati (ETERNAL (English Teaching Journal), 2010)
This article introduces the use of interactive approach in teaching writing, especially paragraph writing. Instead of communicating with the students about the writing product, the teachers of writing subject are mostly correcting the students?óÔé¼Ôäó mistakes and errors in writing. The general idea of writing process is considered very important since it is very helpful for the students. The process approach in teaching paragraph writing is not focusing on the writing product but it is focused on the process of writing, so that this suitable approach that suitable to be applied since writing is a series of process. Keywords: Paragraph, Writing, Process approach, Interactive approaches